The Role of School Administration in Promoting Environmental Culture among Students in the First Cycle of Basic Education from the point of view of Teachers - a Field Study in Lattakia City - أسعد ميرنا; أحلام ياسين; لمى القاضي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research aimed to identify the role of school administration in promoting environmental culture among students in the first cycle of basic education from the point of view of teachers in Lattakia city, and to identify the differences in the points of view of teachers regarding the following research variables (scientific and educational qualification, years of experience). To address the research problem, a questionnaire was used that contained (30) statements, and included the following areas (cognitive, behavioral, and emotional). It was applied to the research sample of (313) teachers, and the descriptive approach was used, after ensuring its validity and reliability. The research concluded that the role of school administration in promoting environmental culture among students in the first cycle of basic education from the point of view of teachers in Lattakia city was to a moderate degree. The results also showed that there were no statistically significant differences between teachers’ estimates of the role of school administration in promoting environmental culture among students, according to the variables (scientific and educational qualification, and years of experience). In light of the results obtained, many recommendations were made, the most important of which were raising the level of environmental culture for students, involving them in classroom and extracurricular environmental activities, and holding training courses for administrative and teaching staff on environmental awareness and education